Lamiaceae: An Insight on Their Anti-Allergic Potential and Its Mechanisms of Action - Sim, Lee Yen; Abd Rani, Nur Zahirah; Husain, Khairana (Frontiers in Pharmacology, 2019)
The prevalence of allergic diseases such as asthma, allergic rhinitis, food allergy and atopic dermatitis has increased dramatically in recent decades. Conventional therapies for allergy can induce undesirable effects and hence patients tend to seek for natural compounds as alternative medicine. Considering the fact above, there is an urgency to discover potential medicinal plants as future candidates in the development of novel anti-allergic therapeutic agents. Lamiaceae family, the mint family, is a diverse plant family which encompasses more than 7000 species and with a cosmopolitan distribution. A number of species from this family has been widely employed as ethnomedicine against allergic inflammatory skin diseases and allergic asthma in traditional practices. Phytochemical analysis of Lamiaceae family has reported the presence of flavonoids, flavones, flavanones, flavonoid glycosides, monoterpenes, diterpenes, triterpenoids, essential oil and fatty acids. Numerous investigations have highlighted the anti-allergic activities of Lamiaceae species with their active principles and crude extracts. Henceforth, this review with an ultimate aim of compiling the up-to-date (2018) findings of published scientific information about anti-allergic activities of Lamiaceae species. Apart from that, the botanical features, medicinal uses, chemical constituents and toxicological studies of Lamiaceae species were also documented. The method employed for data collection in this review was mainly through exploration of databases of PubMed, Ovid and Scopus. Besides, additional research studies were obtained from the reference lists of retrieved articles. In the light of this review, the comprehensive summarization here serves as a useful resource for better understanding on Lamiaceae species. The anti-allergic mechanisms related to Lamiaceae species are also reviewed extensively which aids in future exploration of anti-allergic potential of Lamiaceae species.